The Ethics of Animal Use in Research: Perspectives from Islamic Education and Modern Science - Tareq Alsokari; Ahmad Hamed; Muhammad Fahim Ahmad (Khalifa Journal of Islamic Education, 2025)
The use of animals as research objects in the world of science, such as biology and health, is common practice. However, the problem that often arises is the lack of knowledge of researchers regarding ethics or the correct procedure for using animals as research samples. This article precisely discusses how to use animals in research without violating the ethics that have been regulated by Islam and the provisions of science. This article was written using a qualitative method with a content analysis approach. Data was taken from the framework of Islamic and scientific theoretical concepts, scientific articles related to the issue of animal use, organizational provisions, and international law regarding animal protection as research samples. All data collected is carried out by analysis interactive model Milles & Hubberman assisted by NVIVO 12.0 Software. This finding resulted in seven ethical uses of animals in research; i) reciting tauhid sentence, ii) not using sick animals, iii) using sharp surgical tools, iv) hiding from the eyes of animals, v) minimizing the quantity of animal use, vi) using the euthanasia method, vii) handling post-surgical management. These seven ethics can be used as a reference for researchers in the use of animals in a study, to guarantee and ensure that animals are treated with proper and good ethics.